Development profiles of two cowpea pests on resistant and susceptible Vigna genotypes under constant temperatures - Jackai, L.E.N.; Inang, E.E. (Wiley, 1992)
The growth and development of Clavigralla tomentosicollis Stäl (Hemiptera: Coreidae) and Maruca testulalis Geyer (Lepidoptera: Pyralidae) were studied under laboratory conditions using three cultivated Vigna varieties (IT84E‐124, TVu 1890, MRx 10‐85S) and one wild variety (TVNu 72) under a range of temperatures: 19°C, 22°C, 25°C, 28°C, 31°C, 34°C, 37°C, 40°C and 43°C. IT84E‐124 served as the susceptible and TVNu 72 as the resistant control for both insects. Development time of C. tomentosicollis ranged between 7 days at 37°C to 26 days at 19°C, and decreased with increasing temperature up to an upper temperature threshold of 37°C. The lower temperature threshold for development of C. tomentosicollis was estimated from regression curves to be ca 18.5°C, while the upper threshold was between 34°C and 37°C, the point where nymphal survivorship started to decline. Although 19°C and 22°C gave 90% and 80% survival, respectively, the duration of development at these temperatures was almost twice that reported under field conditions. Adult weights followed an inverse relationship with temperature. Third instar larvae of M. testulalis, obtained after rearing on artificial diet for 7 days prior to feeding on the plants, began to pupate 3 days after infestation at 28, 31 and 34°C. However, adults were obtained only at 22°C and 28°C. Temperatures above 34°C were lethal to the larvae which dried out prior to pupating. The lower temperature threshold determined by regression for pupae was 15.6°–17.8°C on both IT84E‐124 and MRx 10–85S. Upper temperature threshold was estimated to be between 28 and 34°C at which no adult emergence was obtained. Female pupae were larger than males and temperature did not appear to influence sex ratio. Thermal requirements, expressed in degree days (DD), increased with temperature for C. tomentosicollis up to 31°C on all varieties. Degree days for M. testulalis pupae were of a lower magnitude than those computed for C. tomentosicollis.